SPATIAL EXPRESSION OF MATRIX AND MATRIX RECEPTOR PROTEINS IN THE DEVELOPING SYNOVIAL JOINT - Robins, Joshua Eli (East Carolina University, 2013)
Little is understood about the complex spatial and temporal molecular interactions necessary to form a fully functional synovial joint. Understanding molecular pathways and signaling within the developing joint continues to be an area of constant discovery. Versican is a molecule with strong expression in the extracellular matrix (ECM) that has proven necessary for proper joint development. The current study set out to discover gene expression patterns of ECM genes affected by the manipulation of versican. Five genes were chosen based on fold change differences identified from the results of an in-house 2010 microarray study. The microarray study evaluated gene expression differences when the G1 domain of versican was up-regulated in developing joint tissues using a recombinant adenoviral vector, and when the gene was silenced using adeno-shRNA. The five genes of interest were thrombospondin-3, discoidin domain receptor-2, sushi domain containing 5, matrix remodeling associated 5 and matrilin-4. In situ hybridization was performed on sagittal wing sections of HH35 (e9) chick embryos in an attempt to localize gene expression within the developing elbow joint. Results demonstrate gene expression was present in the developing elbow region for each of the five genes of interest. Furthermore mRNA localization for each of the five genes extended into surrounding tissues including the ectoderm, dermis, skeletal muscle, perichondrium, and chondrocytes. This study was undertaken to provide further insight into potential downstream effects of versican activity within the developing joint, as well as provide additional information on the presently limited knowledge surrounding the 5 genes of interest and their role in joint development.
Keywords: Biology; Developmental biology; Molecular biology; Biology, Molecular; Gene expression; Genetic regulation; Joints; Embryology